Reliability of Trunk Muscle Electromyography in the Loaded Back Squat Exercise - Clark, D.; Lambert, M. I.; Hunter, A. M. (International Journal of Sports Medicine, 2016)
Trunk muscle activation (TMA) has been reported during back squat exercise, however reliability and sensitivity to different loads alongside kinematic measures has not. Hence the aim was to determine the interday reliability and load sensitivity of TMA and kinematics during back squats. 10 males performed 3 test sessions: 1) back squat 1RM, 2) and 3) 3 reps at 65, 75, 85 and 95% of system mass max (SMmax). Kinematics were measured from an electrogoniometer and linear transducer, and surface electromyography (sEMG) recorded 4 muscles of the trunk: rectus abdominis (RA), external oblique (EO), upper lumbar erector spinae (ULES) and lumbar sacral erector spinae (LSES), and a reference leg muscle, the vastus lateralus (VL). sEMG amplitude was root mean squared (RMS). No differences (p>0.05) found between tests for any kinematic and RMS data. CV demonstrated moderate interday reliability (~16.1%) for EO, LSES and ULES but not RA (29.4%) during the velocity-controlled eccentric phase; whereas it was moderately acceptable for just LSES and ULES (~17.8%) but not RA and EO (27.9%) during the uncontrolled concentric phase. This study demonstrated acceptable interday reliability for kinematic data while sEMG for most trunk muscle sites was moderately acceptable during controlled contraction. sEMG responded significantly to load.
Keywords: back squat; neuromuscular; trunk muscles; electromyography; electrogoniometry